(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Prenatal substance use is a public health problem deserving the highest priority of attention because it poses devastating risks of maternal and fetal consequences. Situational analysis of current substance use in pregnancy and its risk factors is essential for effective preventive strategies for maternal and child health. This study explored the prevalence of risky substance use (caffeine, alcohol, and tobacco) along with associated factors patterning among pregnant women in the middle zone of Northeastern Thailand. Method: This cross–sectional study was conducted in 58 district hospitals located in the middle zone of northeastern Thailand. The participants were 944 pregnant women attending antenatal clinics chosen based on consecutive sampling. Data collection used a questionnaire, and data analysis used multiple logistic regression. Result: More than two-thirds of the pregnant women (70.1%) reported current substance use, including caffeine (61.6%), alcohol (20.7%), and tobacco (3.3%). Risk factors such as family caffeine use (AOR=2.83, 95%CI: 2.02-3.97) and couple relationship (AOR=1.58, 95%CI: 1.07-2.33) were found to be associated with caffeine in use risk, while marital status (AOR=2.53, 95%CI: 1.11-5.77), couple relationship (AOR=2.27, 95%CI: 1.05-4.91), and family alcohol use (AOR=3.54, 95%CI: 1.49-8.42) were those associated with alcohol in use risk. It was notable that while family tobacco use (AOR=3.85, 95%CI: 1.05-14.06) was associated with tobacco in use risk, age was found to be its protective factor (AOR=0.31, 95%CI: 0.10-0.95) among those in the tobacco use risk group. Conclusion: Currently there is strong evidence about the risky substance use during pregnancy. Modification solutions for suitable consumption behavior should targeted pregnant women with family substance use, poor couple relationships, single status and more than 20 years, old.